PENGARUH WORD OF MOUTH DAN PRODUCT KNOWLEDGE TERHADAP KEPUTUSAN PEMBELIAN SEPEDA LISTRIK U-WINFLY DI SUMENEP SERTA PERAN CITRA MEREK SEBAGAI VARIABEL MEDIASI - Siti Nor Jannah; Edy Purwanto (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Wiraraja, 2026)
Transportation technology continues to change, now a practical and energy-efficient form of transportation has emerged, namely electric bicycles. A person's decision to purchase an electric bicycle is not only based on personal needs and desires, but is also influenced by social and psychological factors such as word of mouth, in addition to a positive brand image and how much consumer knowledge about the product they want to buy can also influence consumer purchasing decisions. This study aims to determine the impact of word of mouth and product knowledge on purchasing decisions and brand image as a mediating variable. The research methodology uses quantitative techniques. The population in this study are customers who have purchased and used U-Winfly electric bicycles in Sumenep. The sample used was 105 individuals. Data were analyzed using Smart PLS. The research results show that word of mouth has a positive and significant impact on purchasing decisions, product knowledge does not have a significant influence on purchasing decisions, word of mouth and product knowledge have a positive and relevant influence on brand image. And brand image can mediate the influence of word of mouth and product knowledge on purchasing decisions for U-Winfly electric bicycles in Sumenep.